Analisis Determinan Praktik Sustainable Reporting pada Perusahaan Manufaktur di Indonesia - Rizal, Samsul; Indriyanto, Erwin (SENTRI: Jurnal Riset Ilmiah, 2025)
The research study aims to analyze the influence of Good Corporate Governance (GCG) mechanisms, Female Directors, Profitability, and Leverage on Sustainable Reporting in Manufacturing Companies in the Consumer Goods Industry Sector Listed on the Indonesia Stock Exchange in 2021 - 2023. There are 126 samples with a purposive method, and the data used is secondary data obtained through companies on the Indonesia Stock Exchange website www.idx.co.id and their respective company websites. The data analysis technique is the Warp Partial Least Square (WarpPLS) model with two modeling models, namely outer model and inner model analysis. The results of this study indicate that the Audit Committee has no effect on Sustainable Reporting, Independent Commissioners have an effect on Sustainable Reporting, Female Directors have an effect on Sustainable Reporting, Profitability has no effect on Sustainable Reporting, and Leverage has an effect on Sustainable Reporting. The results of this study are expected to be a consideration for companies so that they can pay attention to internal and external factors that can affect Sustainable Reporting.